EKSPERIMENTASI PEMBELAJARAN STAD DENGAN MEDIA POWER POINT DAN MODEL BANGUN RUANG MATERI BANGUN RUANG SISI LENGKUNG DITINJAU DARI GAYA BELAJAR - Mardi, Mardi; Mardiyana, Mardiyana; Triyanto, Triyanto (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objective of this research are to investigate: (1) which one that is more effective in teaching geometry, the STAD type of cooperative learning model with Power Point media or that with Geometrical Model media or that with Conventional media, (2) which learning style results in a better learning achievement and (3) which media used in the STAD learning model results in a better learning achievement in each learning style of the students.This research used the quasi-experimental method. The population of this research was the 9th-grade students of the state junior secondary schools in Ngawi regency in the academic year of 2012/2013. The samples of this research consisted of 250 students who were divided into 85 students of the first experiment class, 83 students of the second experiment class, and 82 students of the control class. The samples were taken by using stratified cluster random sampling. The data of this research were gathered through documentation, test, and questionnaire. The hypothesis of this research were tested by using unbalanced Two-way Analysis of Variance. Conclusions drawn are as follows: (1) the STAD learning model with the Power Point media is better than the STAD learning models with the Geometrical Model and the Conventional media whereas the STAD learning model with the Geometrical Model media is equal to the STAD learning model with the Conventional media; (2) the students with the kinesthetic learning style have a better learning achievement than those with the visual and auditory learning styles whereas the students with the visual learning style have an equal learning achievement to those with the auditory learning style; (3) the STAD learning model with the Power Point media results in a better learning achievement than that with the Conventional media whereas the STAD learning model with the Power Point media results in an equal learning achievement to that with the Geometrical Model media and the STAD learning model with the Power Point media results in an equal learning achievement to that with the Conventional media in the visual learning style; (4) the STAD learning model with the all of the three types of media results in an equal learning achievement in the auditory learning style; and (5) the STAD learning model with the Geometrical Model media results in a better learning achievement than that with the Conventional media whereas the STAD learning model with the Power Point media results in an equal learning achievement to that with the Geometrical Model media and the STAD learning model with the Power Point media results in an equal learning achievement to that with the Conventional media in the kinesthetic learning style.Keywords: STAD, Power Point media, Geometrical Model media and learning style.